Identification of lncRNA biomarkers in hepatocellular carcinoma by comprehensive analysis of the lncRNA-mediated ceRNA network - Ye, Dingde; Liu, Yaping; Chen, Yanuo; Li, Guoqiang; Sun, Beicheng; Peng, Jin; Xu, Qingxiang (Frontiers in Genetics, 2022)
Accumulating evidence indicates that lncRNAs can interact with miRNAs to regulate target mRNAs through competitive interactions. However, this mechanism remains largely unexplored in hepatocellular carcinoma (HCC). Long non-coding RNAs (lncRNAs) act as competing endogenous RNAs (ceRNAs), which play a significant role in tumorigenesis and development. The purpose of our study was to determine potential lncRNA biomarkers to predict the prognosis of HCC by comprehensive analysis of a lncRNA-mediated ceRNA network. Differentially expressed RNA datasets were obtained using the edgeR package to analyze 370 HCC tissues and 50 adjacent non-HCC tissues from The Cancer Genome Atlas (TCGA). A total of 947 lncRNAs, 52 miRNAs, and 1650 mRNAs were differentially expressed between HCC tissues and adjacent non-HCC tissues. The novel constructed ceRNA network incorporated 99 HCC-specific lncRNAs, 4 miRNAs, and 55 mRNAs. Survival analysis identified 22 differentially expressed mRNAs, 4 miRNAs, and 9 lncRNAs that were correlated with overall survival (OS) time in patients with HCC (p<.05). Gene ontology (GO) and KEGG pathway enrichment analyses were performed to elucidate the potential functions of these differentially expressed genes in HCC. Univariate and multivariate Cox regression analysis showed that 16 lncRNAs were related to the prognosis of OS, and they were retrieved to construct a predictive model to predict the OS in HCC patients. In conclusion, ceRNAs contributed to the tumorigenesis and development of HCC and a model with 16 lncRNAs might be potential biomarker for predicting the prognosis of HCC. These findings support the need for further studies on the mechanisms involved in the regulation of HCC by ceRNAs.